Juncus fascinatus (Juncaceae), a new combination in Juncus sect. Ozophyllum and notes on morphologically similar species - Knapp, Wesley Wesley (Phytotaxa, 2014)
Please note the figure legend for Fig. 7 (page 253): FIGURE 7. Specimen of Juncus paludosus (A) with inserts showing mature capsule (B), leaf auricle (C) and leaf septa (D). Specimen photo R. Kral 96539B DOV, capsule and auricle A. Curtis 4940 DOV. Scale bar = 1 mm. Should read: FIGURE 7. Specimen of Juncus polycephalos (A) with inserts showing mature capsule (B), leaf auricle (C) and leaf septa (D). Specimen photo R. Kral 96539B DOV, capsule and auricle A. Curtis 4940 DOV. Scale bar = 1 mm.